2014
DOI: 10.1007/s11682-014-9340-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of motor familiarity during simple finger opposition tasks

Abstract: Humans are more familiar with performing (and observing) index-thumb than with any other finger to thumb grasping and the effect of familiarity has not been tested specifically with simple and intransitive actions. The study of simple and intransitive motor actions (i.e. simple actions without need of object interaction) provides the opportunity to investigate specifically the brain motor regions reducing the effect of non-motor aspects that are related with more complex and/or transitive motor actions. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…hopping, jumping, push-ups). Differences in motor familiarity have also been shown to relate to variation in brain activation (Plata Bello et al 2015). We ruled out both variation in motor familiarity and/or poor physical fitness (as a result of low motivation to be physically active) as an explanation for the motor profile; these explanations cannot account for the whole motor profile, neither do they offer a syndrome-specific explanation for the motor profile observed.…”
Section: Discussionmentioning
confidence: 99%
“…hopping, jumping, push-ups). Differences in motor familiarity have also been shown to relate to variation in brain activation (Plata Bello et al 2015). We ruled out both variation in motor familiarity and/or poor physical fitness (as a result of low motivation to be physically active) as an explanation for the motor profile; these explanations cannot account for the whole motor profile, neither do they offer a syndrome-specific explanation for the motor profile observed.…”
Section: Discussionmentioning
confidence: 99%
“…If this region has the same function in monkeys and humans, its higher activation in Bite OFF could reflect a more difficult planning of the finger to thumb sequence. Indeed, fMRI experiments in humans have shown that regions overlapping with the significant clusters in BA 6 are activated during planning and execution of finger and hands movements (Jankowski et al, 2009; Plata Bello et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it captures the main functionalities of premotor/motor and posterior parietal (PPC) regions, such as the population vector coding processes and sensorimotor predictions based on copies of descending neural commands; respectively (Georgopoulos et al 1986, Sirigu et al 1996, Wolpert and Miall 1996. More precisely, consistent with the motor neuroscience literature, our fronto-parietal neural network model includes frontal regions considered as M1/PMC (inverse model; Bullock et al (1993)) and a region hypothesized as the PPC (forward model; Sirigu et al (1996), Blakemore and Sirigu 2003) which are both important in upper-extremity control, including for the hand/fingers (Catalan et al 1998, Abela et al 2012, Cunningham et al 2013, Plata Bello et al 2014. During actual movements, the prefrontal (PFC) regions specify the desired target to reach and send this information to M1/PMC which computes the corresponding joint command signals that are then sent to move the finger.…”
Section: Methodsmentioning
confidence: 93%